Analisis Jenis Kerusakan Alat Berdasarkan Diagram Pareto - Aji Saputra Jefri; Indra Feriadi; Harwadi Harwadi (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Offshore tin mining operations rely heavily on the performance of Production Suction Dredgers as the main production units. The reliability of mechanical production equipment plays a crucial role in maintaining operational continuity and achieving production targets. Recurrent equipment failures can lead to increased downtime, reduced operating hours, and decreased vessel productivity. This study aims to analyze the most dominant types of mechanical equipment failures on KIP Timah 07 using the Pareto Diagram as a basis for determining maintenance priorities. The research method employed is descriptive quantitative with a case study approach. The analyzed data consist of secondary data obtained from daily logsheets, technician work reports, machine operating hour records, and downtime reports during the observation period. Failure data were classified based on failure types, and their frequency, percentage, and cumulative percentage were calculated and presented using a Pareto Diagram. The results indicate that gearbox failure is the most dominant type of failure, contributing 58.88% of the total failure occurrences. In addition, failures in the soil pump bearing block and cutter hydraulic pump also contribute significantly, resulting in a cumulative contribution of 79.44%. Based on these findings, maintenance activities should be prioritized on the dominant components to reduce downtime and improve the reliability and operational productivity of KIP Timah 07.